Spatial management in small-scale fisheries: A potential approach for climate change adaptation in Pacific Islands. (February 2018) - Le Cornu, Elodie; Doerr, Angee N.; Finkbeiner, Elena M.; Gourlie, Don; Crowder, Larry B.
Abstract: Small-scale fisheries are undeniably important for livelihoods, food security and income around the globe. However, they face major challenges, including global market and demographic shifts, policy changes and climate variations that may threaten the wellbeing, health and safety of fishing communities. Over the years, various forms of spatial management have been implemented in small-scale fisheries as a potential solution to problems afflicting these systems. The benefits of such approaches can be numerous for both ecosystems and coastal communities. In addition to the persistent challenges influencing small-scale fisheries practices, the emerging effects of climate change pose serious risks to coastal ecosystems and fishing communities, especially in low-lying islands. Despite a growing recognition of both the benefits of spatial management and the adverse effects of climate change on small-scale fisheries, integration of these concepts in a consistent and comprehensive way has not yet occurred. Spatial management has the potential to foster small-scale fisheries adaptation to climate change, however, in the face of such a global and transboundary phenomenon, management strategies will need to be carefully designed and implemented. First, key considerations for climate-informed spatial management in small-scale fisheries were identified. Second, these key considerations were illustrated in two selected case studies in Pacific Island countries and territories (i.e. Fiji and Papua New Guinea). Finally, the challenges associated with spatial management in a changing climate are discussed and ways forward for advancing this type of management as a climate adaptation approach for small-scale fisheries in the Pacific and beyond are proposed. Highlights: Climate-informed spatial management can foster small-scale fisheries adaptation in Pacific island countries and territories. Identifying key considerations for spatial management in the context of climate change is critical. Two case studies in Pacific islands illustrate the importance of these key considerations in real-world applications. Bounded approaches in the context of a transboundary phenomenon like climate change still raise serious issues. Dynamic Ocean Management can advance spatial management as a climate adaptation approach in the Pacific.